Nursesâ€™ KAP related to research conduct and utilization: EBNP â€œare we ready yet. - Amel Abouelfettoh, Dr; Elham Al Ateeq, Dr (International Journal of Advanced Nursing Studies, 2018)
Background: Nurses make a positive difference every day and continue to shape the future of healthcare through planning, implementation and dissemination of quality research studies. The practice of evidence-based nursing is determined by the nurseâ€™s clinical experience as well as clinically relevant research knowledge, willingness to apply research to practice, and the skills to do so. No previous studies had been conducted to assess the conduct and utilization of nursing research and EBP in the Eastern province of Saudi Arabia.Objective: Assess current nursesâ€™ research knowledge, attitude, and practice related to research conduct and utilization and to determine individual, organizational and contextual factors that predicts nursesâ€™ ability to conduct and utilize research findings into practice.Methods: Descriptive correlational cross-sectional design utilized to study a convenient sample of 719 nurses working at different health care sectors in the Eastern Region of KSA. [33] Items Research KAP Survey measured nursesâ€™ KAP related to researchÂ© (KAP), a. three level Likert Scale (ranging from one to 3). Score less than 1.66 is â€œlow, 1.67 to 2.33 is â€œmoderateâ€ and 2.34 to 3.0 is â€œhighâ€.Results: A response rate of 89.9% was obtained. Nurses were mostly females, aged between 30 to 40 years. Nursesâ€™ knowledge and attitude levels were moderate (1.78, 1.88 respectively), however the practice was low (1.31). Individual factors explained 77.4% (R2 = .774, F (5)=458, p<.001), contextual factors explained 8% (R2 = .089, F(4)=15.2, p<.001), and organizational factors explained 77.4% of the nurses ability to practice evidence based (R2 = .774, F(5)=458, p<.001).Conclusion: The study findings provide feedback to strengthen nursing research competencies at the regional level and to the Development of nursing research-related policies, guidelines, and educational programs for evidence based nursing practice.Â Â